PED’s paradigm shift as regenerative city models between innovation, green infrastructures and urban form - Pidalà, Andrea Marçel (TeMA - Journal of Land Use, Mobility and Environment, 2025)
In 2007, the European Union launched The Strategic Energy Technology Plan (SET), which is in fact the framework within which some ecological transition policies for the European territory are inserted. Contributing to the ambitious objectives of the European Strategic Energy Technology (SET) Plan, the programme “Positive Energy Neighbourhoods and Neighbourhoods for Sustainable Urban Development” supports the planning, deployment and deployment of 100 Positive Energy Districts by 2025. Even the new Horizon Europe research and innovation plan (which will cover the period 2021-2027), Europe aims to tackle some global challenges affecting our cities and our society with determination: health and safety, digitalisation, energy and climate change in the first place. The Positive Energy Districts are part of this perspective. It is supported by 20 EU Member States and conducted by JPI Urban Europe. The programme involves stakeholders from R&I funding networks, cities, industry, research organisations and citizens’ organisations. In this sense, wanting to focus the interest of this research – of which an extract can be found in these writings – we find a first decisive orientation – at the European level – through the declination of European policies. The paper, starting from the various international strategies promoted by intergovernmental subjects, focuses its attention on the very recent energy transition initiatives in the urban area. By examining some selected case studies, he defines a methodological approach - focused on case studies/good practices - that goes beyond the classic analytical approach by moving towards a more systemic design.